National Minorities: A Chance or Challenge for the Catholic Church - Szabolcs ORBÁN (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2020)
The issue of national minorities in the past century has often given rise to conflicts, becoming a peace-threatening issue and consequently a source of serious distress. Thus, from this perspective, it had become a topic that the churches could not remain silent about. This article aims to present briefly the way in which the Catholic Church related to the national minorities from the perspective of the Catholic social teaching. At first, we will present a few ecclesiastical documents (papal documents, writings, speeches, etc.) that touched upon this topic one way or another during the past more than 100 years. In the light of these, we shall see the main aspects that the Catholic Church deemed to be important to emphasize in relation to minorities. Next, as an example, we shall also mention a few local ecclesiastical documents pointing out the manner in which the general principles are manifest in the toilsome everyday life of the local communities experiencing concrete historical situations. The third part of the study will refer to the important basic principles of social teaching – namely, common good and subsidiarity –, and we will try to pin down certain insights that would guide both the majority and the minority on the path towards the opportunity of welfare, thereby bringing hope for the mitigation of tensions.